Extracellular Vesicles of Mesenchymal Stem Cells Are More Effectively Accessed through Polyethylene Glycol-Based Precipitation than by Ultracentrifugation - Lei Jia; Bo Li; Cong Fang; Xiaoyan Liang; Yingjun Xie; Xiaofang Sun; Wen Wang; Lei Zheng; Ding Wang (Stem Cells International)
Extracellular vesicles (EVs) have been identified as cell-cell communication agents, and EVs derived from mesenchymal stem cells (MSCs) exhibit therapeutic effects similar to those of the cells of origin. Precipitation methods have been used extensively for EV harvests, such as UC- (ultracentrifugation-) or PEG- (polyethylene glycol-) based methods, and the difference in EVs derived from MSCs by UC and PEG is not fully understood. We harvested EVs from amniotic fluid MSCs (AF-MSCs) by UC- or PEG-based precipitation methods and conducted a comparison study of those EVs derived by the two methods: output, RNA, and protein expression of EVs and EV biological reaction in a THP-1-cell model of LPS induction, which was considered an infection model. There was no difference in morphology, size, or specific marker-positive ratio of PEG-EVs and UC-EVs, but PEG obtained more EV particles, protein, and RNA than the UC method. In our THP-1 model of LPS induction, MSC-EVs did not lead to a change in protein expression but inhibited the LPS-induced increase in cytokine secretion. UC-EVs were more effective for TNF-α inhibition, and PEG-EVs were more effective for IL10 inhibition. Thus, our findings provide evidence that PEG-based precipitation is a more efficient mesenchymal stem cell-extracellular vesicle-derived method than UC.